The king of Staten Island [videorecording (DVD)] - Apatow, Judd, 1967-; Davidson, Pete, 1993-; Davidson, Pete, 1993-; Tomei, Marisa; Burr, Bill, 1968-; Powley, Bel, 1992-; Buscemi, Steve, 1957- (Universal Pictures Home Entertainment, 2020)
Scott has been a case of arrested development ever since his firefighter father died when he was seven. He's now reached his mid-20s having achieved little, living with his mother, spending his days smoking weed, hanging with the guys, and secretly hooking up with his girlfriend Kelsey. But when his mother starts dating a loudmouth firefighter named Ray, it sets off a chain of events that will force Scott to grapple with his grief and take his first tentative steps toward moving forward in life.